Jolkinolide B induces reactive oxygen species accumulation and endoplasmic reticulum stress and inhibits MAPK and AKT signaling activation in renal cancer cells - Xuan Wu; Sijing Pan; Xiujuan Li; Jing Liu; Zhigang Wang; Yinghong Lei; Qunchao Mei (Journal of Men's Health, 2024)
To investigate the impact of Jolkinolide B (JB) on renal cell carcinoma (RCC), we treated RCC cell lines with various concentrations of JB (0, 5, 25, 50 and 100 μM) for 24 hours and assessed cell viability using the cell counting kit-8 (CCK-8) analysis. Then, we examined JB’s effects on proliferation, migration, apoptosis, reactive oxygen species (ROS) accumulation, and endoplasmic reticulum (ER) stress through 5-ethynyl-2′-deoxyuridine (EdU) incorporation, transwell migration assays, flow cytometry, ROS level determination, and western blot assays. Furthermore, we investigated the potential mechanism using western blot. Our results showed that JB dose-dependently reduced cell viability in both 786-O and Caki1 cells. Additionally, JB at concentrations of 5, 25 and 50 μM decreased the number of EdU-positive and migrating cells in both cell lines. Additionally, these concentrations of JB increased apoptosis rates, relative protein expressions of cleaved caspase-3 and cleaved caspase-9, ROS levels, and relative protein expressions of C/EBP-homologous protein (CHOP) and activated transcription factor 4 (ATF4) in both 786-O and Caki1 cells. Mechanistically, treatment with all three concentrations of JB significantly downregulated phosphorylated p38 (p-p38)/p38, phosphorylated protein kinase B (p-AKT)/AKT and phosphorylated phosphatidylinositol-3-kinase (p-PI3K)/PI3K in a dose-dependent manner. In summary, JB inhibited proliferation and migration while promoting apoptosis, ROS accumulation, and ER stress in RCC cells, potentially through the inactivation of mitogen-activated protein kinase (MAPK) and AKT signaling pathways.